Air compressor rotor blade light absorption film identification method of aero-engine and preparation of film
By depositing light-absorbing film on the rotor blades of the aircraft engine compressor and using laser sensing technology, the problem of difficult rotor blade bond recognition is solved, fast and accurate identification is achieved, the test run cost and cycle are reduced, and the dynamic balance and reliability of the engine are improved.
Patent Information
- Application Number
- CN202411679710.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The compressor rotor of an aircraft engine deviates from the ideal axis due to the center of mass, resulting in unbalanced excitation force and causing vibration problems. The existing technology lacks effective identification and solutions, resulting in high test run costs and long cycles, which affects delivery progress, quality and cost.
A bond phase sensor is used to emit laser light to the rotor blades, and different blade bond phases are distinguished and identified by deposition of light absorbing films (Cr film and CrN film) on the blade surface.
It realizes rapid and accurate identification of the bond phases of the rotor blades, reduces the cost and cycle of test drives, and improves the dynamic balance and reliability of the engine.
Smart Images

Figure CN119534393A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of identification of compressor blades of aircraft engines, and in particular relates to a method for identifying a light-absorbing film of a compressor rotor blade of an aircraft engine and the preparation of the film. Background Art
[0002] Aircraft engines are known as the "crown jewel of industry" and are the source of power for aircraft. They have a complex structure and are assembled from tens of thousands of parts into components, parts, and units according to the process. The core engine rotor is an important component of the aircraft engine and is assembled from a high-pressure compressor, a combustion chamber, and a high-pressure turbine. The high-pressure compressor compresses the air flowing through it so that the air reaches the optimal compression state and temperature. The compressed air is mixed with the fuel and burned in the combustion chamber, converting chemical energy into internal energy. The speed and pressure of the high-temperature gas provide power for the turbine, which drives the shaft to rotate, and then drives the compressor and combustion chamber and other components to work continuously, forming a continuous combustion cycle. The working efficiency of the core engine rotor determines the compression efficiency of the engine compressor, and then determines the driving power and various performance parameters of the engine.
[0003] As a high-speed rotating machine with a complex structure, aircraft engines work under harsh conditions of high temperature, high pressure, high speed and other high loads for a long time, and are prone to various forms of failure. Due to material unevenness, processing errors, assembly errors and other reasons, the center of mass of the core engine rotor deviates from the ideal axis, and an unbalanced exciting force proportional to the square of the rotation speed will be generated in the rotating state. The direction of the exciting force changes periodically as the rotor rotates. This periodically changing unbalanced exciting force acts on the rotor and causes vibration of the aircraft engine. The vibration problem has always been a difficult problem in the development process of aircraft engines.
[0004] The mechanism of aircraft engine vibration is complex, involving design, component processing and manufacturing, assembly, testing, use and many other links, and there is no good solution. For engines with excessive vibration, the only way is to carry out the cycle of disassembly-troubleshooting-assembly-testing, which is not only inefficient but also extremely expensive. At the same time, excessive vibration during the use of the engine directly affects the reliability and safety of the engine, brings great risks to customers, and greatly increases the cost of engine manufacturing, use and maintenance.
[0005] Balancing the rotor according to the vibration phase characteristic information of the rotor system is an effective means to achieve dynamic balancing of aircraft engines. How to set a reference key phase to effectively distinguish and identify the key phases of different rotor blades is the key to achieving rotor balancing. At present, there is no effective solution. The main method is to identify the blade key phase by adding a phase test run. The cost of a single engine test run is as high as nearly one million yuan, and the cycle is long, which significantly affects the delivery schedule, quality and cost of aircraft engines. Summary of the invention
[0006] In order to solve the deficiencies in the prior art, the present invention provides a method for identifying a light-absorbing film on a compressor rotor blade of an aircraft engine and a method for preparing the film.
[0007] The method for identifying the light-absorbing film on the aviation compressor rotor blades described in the present invention refers to using a key phase sensor to emit a laser to the rotor blades and receive the light signal reflected when the blade tip scans over. The intensity of the light signal reflected by the blades with a light-absorbing film deposited on the surface is reduced, forming a light-absorbing area, which is different from the light signal intensity reflected by other blades without the light-absorbing film deposited, thereby achieving effective distinction and identification of different rotor blades.
[0008] The light-absorbing film has a thickness of less than 10 μm and comprises a Cr film and a CrN film. The Cr film is deposited on the surface of the rotor blade, and the CrN film is deposited on the surface of the Cr film.
[0009] The blade surface includes the blade basin, blade back and inlet and outlet edge rounded parts of the rotor blade.
[0010] The preparation method of the light absorbing film is as follows:
[0011] S1 pretreatment: remove oil stains from the blade surface, protect the non-coated area, and then use argon sputtering to clean and activate the surface of the area where the light-absorbing film is to be deposited;
[0012] S2 Cr film deposition: the Ar gas flow rate is adjusted to reduce the vacuum chamber pressure to 0.1-0.3 Pa, chromium is used as the target material, multi-arc ion plating is performed under the conditions of target current of 180-200A, bias voltage of -200V--400V, duty cycle of 40%, and deposition time of 1-3min, and the Cr film is deposited on the blade surface to enhance the bonding strength between the CrN film and the substrate;
[0013] S3 deposits CrN film: turn off Ar gas, introduce high-purity N2, adjust the vacuum chamber pressure to 0.5-1Pa, perform multi-arc ion plating under the conditions of chromium target current of 180-200A, bias voltage of -200V-400V, duty cycle of 40%, and deposition time of 15-30min, and deposit CrN film on the surface of Cr film; during the deposition of light-absorbing film, adjust N2 pressure to alleviate the interface mismatch problem between CrN and titanium alloy substrate, and improve the film-substrate bonding strength;
[0014] During the deposition process, the target-substrate distance is 200-220 mm; after the deposition is completed, the light-absorbing film is obtained on the surface of the blade.
[0015] S1 preprocessing includes the following specific methods:
[0016] The blades were ultrasonically cleaned with acetone and then dried; the non-deposition area was protected and the blades were clamped on a special deposition device and then vacuumed until the vacuum chamber pressure did not exceed 3×10 -3 High-purity argon gas was introduced at 3 Pa to make its pressure 1-3 Pa, and the sample was sputtered and cleaned for 3 minutes under the conditions of bias voltage of -600 V to -800 V and duty cycle of 40% to activate the surface of the parts and remove surface contamination.
[0017] The light-absorbing film prepared by the multi-arc ion plating method described in the present invention has precisely controllable process parameters, strong bonding with the substrate, thin and uniform thickness, and a smooth surface; it avoids the problems of poor bonding, poor surface roughness, and difficult control of coating thickness uniformity of air sprayed light-absorbing coatings in the prior art, high process temperature of chemical vapor deposition light-absorbing coatings that exceeds the phase change point of the blade substrate material and affects the blade tissue and mechanical properties, and target material poisoning and uneven coating of complex-shaped blades in magnetron sputtering light-absorbing coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a diagram showing the position of the deposition area of the blade in a dedicated deposition device during the coating process.
[0019] Figure 2 This is a positional relationship diagram of the deposition area and non-deposition area of the blade in a dedicated deposition device after coating.
[0020] Figure 3 It is a schematic diagram of the deposition area of the light-absorbing film on a certain type of compressor rotor blade, where area P is the deposition area.
[0021] Figure 4 This is a physical picture of the light-absorbing film deposited in Example 1.
[0022] Figure 5 This is a scanning electron microscope image of the light-absorbing film deposited in Example 1.
[0023] Figure 6 This is a key phase test effect diagram of the engine after the blades deposited with the light-absorbing film in Example 1 are installed on the compressor rotor.
[0024] Figure 7 This is a key phase test effect diagram of the engine after the blades deposited with the light-absorbing film in Example 2 are installed on the compressor rotor.
[0025] Figure 8 This is a key phase test effect diagram of the engine after the blades deposited with the light-absorbing film in Example 3 are installed on the compressor rotor. DETAILED DESCRIPTION
[0026] The present invention intends to deposit a light-absorbing film on two blades of a titanium alloy compressor rotor blade. Before depositing the light-absorbing film on the blade surface by multi-arc ion plating, the oil on the blade surface is first removed and the pre-deposition site is activated. The specific method is as follows:
[0027] In order to reduce the influence of coating process on blade fatigue and vibration frequency, the blade surface is not sandblasted, and only acetone and other solvents are used to clean the surface of the parts to achieve degreasing effect. The blades are evenly spread in a container filled with acetone, and the acetone completely covers the blades. Ultrasonic cleaning is used with a frequency of 20kHz and an output voltage of 320-370V for 5-10 minutes. The washed parts are blown dry with water-free and oil-free compressed air and placed in a clean tray for transfer.
[0028] A special coating device is used to fix the blade in the fixture. The area where the film does not need to be deposited is covered and protected by the fixture, and the deposition area is exposed outside the fixture. The actual picture is as follows Figure 1 and Figure 2 As shown; the schematic diagram is as Figure 3 As shown, deposition occurs only in the P region of the blade body (i.e., the blade basin, blade back, and inlet and exhaust edge chamfers).
[0029] Example 1
[0030] S1 Pretreatment: Spread the blades evenly in a container filled with acetone, completely cover the blades with acetone, and use ultrasonic cleaning with a frequency of 20kHz and an output voltage of 320V for 5 minutes. After the parts are washed, blow dry with water-free and oil-free compressed air and place them in a clean tray for transfer.
[0031] Install the blade on a special coating device. Avoid touching the blade with bare hands during the installation process. Wait until the vacuum chamber pressure reaches 3×10 -3 High-purity argon gas was introduced at 1 Pa to make its pressure 1 Pa, and the surface of the blade substrate on which the light-absorbing film was to be deposited was cleaned by Ar ion beam sputtering for 3 minutes under the conditions of a bias voltage of -600 V and a duty cycle of 40%.
[0032] S2 deposition of Cr film: the Ar gas flow rate was adjusted to reduce the vacuum chamber pressure to 0.1 Pa, the chromium target current was set to 180 A, and the metal Cr film was deposited for 1 min at a bias voltage of -200 V and a duty cycle of 40%.
[0033] S3 deposition of CrN film: turn off the Ar gas, introduce high-purity N2, adjust the vacuum chamber pressure to 0.5 Pa, set the chromium target current to 180 A, and deposit the CrN film for 15 minutes under the conditions of a bias voltage of -200 V and a duty cycle of 40%.
[0034] The target-substrate distance during deposition was 200 mm. After deposition, the equipment was turned off and the blade was removed after cooling.
[0035] The actual photo of the leaf after the light-absorbing film is deposited Figure 4 The SEM image of the cross section of the deposition area is shown in Figure 5 As shown, it can be seen that the film thickness is only about 3μm, and the film thickness is small; although the Cr film layer is very thin, it can effectively improve the bonding strength between the CrN film layer and the blade substrate so that it is not easy to fall off.
[0036] Example 2
[0037] S1 Pretreatment: Spread the blades evenly in a container filled with acetone, completely cover the blades with acetone, and use ultrasonic cleaning with a frequency of 20kHz and an output voltage of 370V for 10 minutes. After the parts are washed, blow dry with water-free and oil-free compressed air and place them in a clean tray for transfer.
[0038] Install the blade on a special coating device. Avoid touching the blade with bare hands during the installation process. Wait until the vacuum chamber pressure reaches 1×10 -3 High-purity argon gas was introduced at 3 Pa to make its pressure 3 Pa, and the sample was cleaned by Ar ion beam sputtering for 3 min under the conditions of bias voltage of -800 V and duty cycle of 40%.
[0039] S2 deposition of Cr film: the Ar gas flow rate was adjusted to reduce the vacuum chamber pressure to 0.3 Pa, the chromium target current was set to 200 A, and the metal Cr film was deposited for 3 min at a bias voltage of -400 V and a duty cycle of 40%.
[0040] S3 deposition of CrN film: turn off Ar gas, introduce high-purity N2, adjust the vacuum chamber pressure to 1Pa, set the chromium target current to 200A, and deposit the CrN film for 30 minutes under the conditions of -400V bias and 40% duty cycle.
[0041] The target-substrate distance during deposition was 220 mm. After deposition, the equipment was turned off and the blade was removed after cooling.
[0042] Example 3
[0043] S1 Pretreatment: Spread the blades evenly in a container filled with acetone, completely cover the blades with acetone, and use ultrasonic cleaning with a frequency of 20kHz and an output voltage of 360V for 8 minutes. After the parts are washed, blow dry with water-free and oil-free compressed air and place them in a clean tray for transfer.
[0044] Install the blade on a special coating device. Avoid touching the blade with bare hands during the installation process. Wait until the vacuum chamber pressure reaches 2×10 -3 High-purity argon gas was introduced at 2 Pa to make its pressure 2 Pa, and the sample was cleaned by Ar ion beam sputtering for 3 min under the conditions of bias voltage of -700 V and duty cycle of 40%.
[0045] S2 deposition of Cr film: the Ar gas flow rate was adjusted to reduce the vacuum chamber pressure to 0.2 Pa, the chromium target current was set to 190 A, and the metal Cr film was deposited for 2 min at a bias voltage of -300 V and a duty cycle of 40%.
[0046] S3 deposition of CrN film: turn off the Ar gas, introduce high-purity N2, adjust the vacuum chamber pressure to 0.8 Pa, set the chromium target current to 190 A, and deposit the CrN film for 25 minutes under the conditions of a bias voltage of -300 V and a duty cycle of 40%.
[0047] The target-substrate distance during deposition was 210 mm. After deposition, the equipment was turned off and the blade was removed after cooling.
[0048] The titanium alloy blades deposited with light-absorbing films in Examples 1, 2, and 3 were respectively installed on the compressor rotors of three aircraft engines, and a key phase sensor was used to emit lasers to the rotor blades and receive the light signals reflected when the blade tips passed by. The test results are as follows: Figure 6 , Figure 7 , Figure 8 As shown in the figure, the vertical axis represents the relative intensity of the reflected signal, and the horizontal axis represents the relative position of the rotor blades during the test cycle. It can be seen from the figure that due to the light absorption of the film, the relative intensity of the reflected signal of the blades deposited with the light-absorbing film is significantly lower than that of other blades, and there is a significant difference in the reflected signal of the blades without the film, thereby distinguishing and identifying the rotor blades. This identification method can quickly locate the parts that need to be weighted in the dynamic balancing of the engine. The light-absorbing film composed of Cr film and CrN film has a small film thickness and is locally coated on the blade, which reduces the impact on the weight and fatigue life of the blade; under the high-load working environment of the compressor rotor blades greater than 10,000rpm, the compressor rotor blades of the three engines can still be effectively positioned.
Claims
1. A method for identifying the light-absorbing film on the compressor rotor blades of an aircraft engine, characterized in that: The light absorbing film comprises a Cr film and a CrN film, wherein the Cr film is deposited on the surface of the rotor blade, and the CrN film is deposited on the surface of the Cr film; A key phase sensor is used to emit laser to the rotor blades and receive the light signal reflected when the blades are scanned. The intensity of the light signal reflected by the blades with a light-absorbing film deposited on the surface is low, which is different from the intensity of the light signal reflected by other blades without the light-absorbing film deposited, thereby achieving the distinction and identification of different rotor blades.
2. The method for identifying the light-absorbing film on the compressor rotor blades of an aircraft engine according to claim 1, characterized in that: The light absorption film has a thickness of less than 10 μm.
3. The method for identifying the light-absorbing film on the compressor rotor blades of an aircraft engine according to claim 1, characterized in that: The blade surface includes the blade basin, blade back and inlet and outlet edge rounded parts of the rotor blade.
4. The method for preparing a light-absorbing film according to any one of claims 1 to 3, characterized in that: Includes the following: S1 pretreatment: protect the non-coated area of the blade, and sputter clean to activate the surface of the area where the light-absorbing film is to be deposited; S2 deposition of Cr film: using chromium as the target material, multi-arc ion plating is performed under the conditions of target current of 180 to 200 A and bias voltage of -200 V to -400 V to deposit the Cr film on the blade surface; S3 deposition of CrN film: N2 is introduced, and multi-arc ion plating is performed under the conditions of a chromium target current of 180 to 200 A and a bias voltage of -200 V to -400 V to deposit a CrN film on the surface of the Cr film.
5. The method for preparing a light-absorbing film according to claim 4, characterized in that: When depositing the Cr film in step S2, the Ar gas flow rate is first adjusted to reduce the pressure of the vacuum chamber to 0.1-0.3 Pa and then the Cr film is deposited. The duty cycle is 40% and the deposition time is 1-3 minutes.
6. The method for preparing a light-absorbing film according to claim 4, characterized in that: When depositing the CrN film in step S3, the Ar gas is first turned off, and N2 is introduced. The pressure of the vacuum chamber is adjusted to 0.5-1 Pa before depositing the CrN film. The duty cycle is 40% and the deposition time is 15-30 min.
7. The method for preparing a light-absorbing film according to claim 4, characterized in that: The target-substrate distance during the deposition process is 200-220 mm.
8. The method for preparing a light-absorbing film according to claim 4, characterized in that: Step S1 pretreatment includes the following specific methods: ultrasonically clean the blade with acetone to protect the non-deposition area, clamp the blade on the deposition device and then evacuate the vacuum chamber until the pressure in the vacuum chamber does not exceed 3×10 -3 Argon gas was introduced at 3 Pa to make its pressure 1-3 Pa, and the sample was sputtered and cleaned under the conditions of bias voltage of -600 V to -800 V and duty cycle of 40% to activate the blade surface.
Citation Information
Patent Citations
Method for preparing multi-arc ion plating aluminium titanium chrome silicon yttrium nitride multi-component ultra-hard reaction film
CN101230448A
Method for preparing of low stress chromium nitride multilayer hard film
CN101338412A
Diffuse reflection hard light space-time sampling measuring method and device based on rotary blade
CN103575386A
Method for depositing functionally-graded nano-multilayer coating on surface of steel workpiece and product comprising functionally-graded nano-multilayer coating
CN105568231A
Rotating speed signal generation and measurement method with key phase function based on blade tip timing
CN114878853A